ENCODING AND DECODING INFORMATION IN MODERN MEDIA: ADVANTAGES OF INTERNET MEDIA - Рум’янцева, С.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The nature of the communicative process of coding and decoding information of the media is analyzed in this article. Also it determinates the basic errors that are made by communicators and recipients of the communicative process. The global network Internet and its media are also under precise attention as one of the leading and most perspective mass media. In addition, both positive and negative circumstances that could affect the encoding and decoding of information between broadcasters and consumers are considered in given article.